Improving Footwork Learning Outcomes in Badminton Through Shuttle Run Training Model Among Eighth Grade Students of State Junior High School 13 Palopo - Dery Nugroho Zulkarnain; Irsan Kahar; Nur Saqinah Galugu (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
The purpose of this study is to determine whether shuttle run training can improve footwork learning outcomes in badminton among eighth grade students of State Junior High School 13 Palopo. This study was conducted at State Junior High School 13 Palopo over a period of 1 month. The research employed Classroom Action Research (CAR) methods, encompassing two cycles, each consisting of two meetings. The research population comprised eighth grade students of State Junior High School 13 Palopo, with a total of 13 students, including 7 boys and 6 girls. The instruments or measurement tools used in this study included rackets, shuttlecocks, and cones. The assessment points utilized affective, cognitive, and psychomotor evaluation sheets. The results obtained through two cycles showed that in the first cycle, 7 students met the Minimum Mastery Criteria (MMC)  while 6 students did not. However, in the second cycle, 12 students met the MMC and 1 student did not. The MMC was determined based on the lesson plan prepared by the school teacher, where a score of ≥77 meets the MMC and a score of ≤77 does not meet the MMC. Based on this criterion, from the second cycle, 12 students met the MMC and 1 student did not meet the MMC out of a total of 13 students based on the three domains tested, namely cognitive, affective, and psychomotor, the average score was 82.5.